Correlation between Apolipoprotein B Levels with Coronary Lesion Area Based on the Gensini Scores in Coronary Heart Disease Patients - Siallagan, Delpiana; Siregar, Jelita; Hasan, Refli (TALENTA Publisher, Universitas Sumatera Utara, 2023)
Background: Coronary heart disease (CHD) is caused by atherosclerosis. apolipoprotein B (Apo B) is a large glycoprotein, that plays a role in lipoprotein metabolism and human lipid transport, reflecting atherogenic cholesterol transport. The Gensini scoring system has the highest correlation with the severity of coronary artery stenosis as assessed by angiography. This study aims to determine the correlation between apolipoprotein B levels with the area of ​​coronary lesions based on the Gensini score in patients with CHD Methods: This research is an observational study with cross cross-sectional data collection method of 76 coronary heart disease patients who were treated at H. Adam Malik General Hospital Medan (December 2021 – April 2022). Examination of the Apo B value was carried out by the immunoturbidimetry method (Architect). Coronary lesion area calculated from coronary angiography with Gensini score. The research was conducted after obtaining ethical approval and informed consent. Result: There were 57 male subjects (75 %). The mean age of the subjects was 56.17 years with the youngest age being 24 years and the oldest being 77 years. Most of the subjects who experienced STEMI amounted to 38 people (50 %). The mean Apo B level was 89.18 mg/dL. The mean Gensini score was 62.84. By using the Pearson correlation test, it was found that a significant correlation was found between Apo B and Gensini score, r = 0,288 (p = 0.012) Conclusions: There was a significant correlation between the levels of Apo B and coronary artery lesions based on the Gensini score. Apo B examination and Gensini score can be used as a risk assessment of severity in CHD patients. Further research is needed to involve a larger number of coronary heart disease patients.